Morphological changes in the spiracles of Anopheles gambiae s.l (Diptera) as a response to the dry season conditions in Burkina Faso (West Africa). Issue 1 (December 2016) - Mamai, Wadaka; Mouline, Karine; Parvy, Jean-Philippe; Le Lannic, Jo; Dabiré, Kounbobr; Ouédraogo, Georges; Renault, David; Simard, Frederic
Abstract Background Survival to dry season conditions of sub-Saharan savannahs is a major challenge for insects inhabiting such environments, especially regarding the desiccation threat they are exposed to. While extensive literature about insect seasonality has revealed morphologic, metabolic and physiological changes in many species, only a few studies have explored the responses following exposure to the stressful dry season conditions in major malaria vectors. Here, we explored morphological changes triggered by exposure to dry season conditions inAn. gambiae s.l. mosquitoes by comparing females reared in climatic chambers reflecting environmental conditions found in mosquito habitats during the rainy and dry seasons in a savannah area of Burkina Faso (West Africa). Results Using scanning electron microscopy (SEM) and confocal imaging, we revealed significant changes in morphological features of the spiracles in femalesAn. gambiae s.l. exposed to contrasted environmental conditions. Hence, the hairs surrounding the spiracles were thicker in the three species when raised under dry season environmental conditions. The thicker hairs were in some cases totally obstructing spiracular openings. Specific staining provided evidence against contamination by external microorganisms such as bacteria and fungi. However, only further analysis would unequivocally rule out the hypothesis of experimental artifact. Conclusion Morphological changes in spiracular features probably help to limit body water loss during desiccating conditions, therefore contributing to insect survival. Differences between species within theAn. gambiae complex might therefore reflect different survival strategies used by these species to overcome the detrimental dry season conditions in the wild.